Detection and comparison of the sensory quality of wild and farmed brown trout (Salmo trutta) by consumers - Pohar, Jurij (Acta agriculturae Slovenica, 2011)
To compare the sensorial quality of wild and farmed brown trout 34 consumer were asked to decide which of the two samples presented to them in double blind test was preferred regarding appearance, aroma, juiciness, mouth feeling and general impression if difference in mentioned traits between both samples was detected. Results showed that for all traits at least 75% of consumers stated that they noticed difference. For appearance and aroma wild trout was preferred, for juiciness and mouth feeling farmed trout was favored. General impression of wild brown trout was favored by 15 consumers, while 16 consumers regarding this trait preferred farmed brown trout. Meaning and importance of results from consumers' panel test for positioning of products from fish farming and fisherz is discussed.
Keywords: ribe; potočna postrv; Salmo trutta; senzorična analiza; porabniki; reja; ribolov